2013
DOI: 10.1111/ahg.12041
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evaluation and Application of Posterior Cranial Fossa Traits as Endophenotypes for Chiari Type I Malformation

Abstract: SUMMARY Chiari Type I Malformation (CMI) is characterized by herniation of the cerebellar tonsils through the base of the skull. Although cerebellar tonsillar herniation (CTH) is hypothesized to result from an underdeveloped posterior cranial fossa (PF), patients are frequently diagnosed by the extent of CTH without cranial morphometric assessment. We recently completed the largest CMI whole genome qualitative linkage screen to date. Despite an initial lack of statistical evidence, stratified analyses using cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 31 publications
1
43
0
1
Order By: Relevance
“…Multiple regions of the PF were associated with blood class, including the Boogaard’s angle, tentorium, and the basion to the reference line. Similar to the dura analysis, all of these PF traits were previously found to be heritable in a collection of CMI families [14]. The only clinical association observed with blood class was paternal age; limitations of this analysis were described in detail above.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Multiple regions of the PF were associated with blood class, including the Boogaard’s angle, tentorium, and the basion to the reference line. Similar to the dura analysis, all of these PF traits were previously found to be heritable in a collection of CMI families [14]. The only clinical association observed with blood class was paternal age; limitations of this analysis were described in detail above.…”
Section: Resultsmentioning
confidence: 83%
“…All measurements were performed by one trained researcher and then confirmed by a board certified neuroradiologist (D.E.). Measurements were taken for right and left herniation (also computed minimum and maximum herniation), as well as the foramen magnum, tentorium, supraoccipital bone, clivus, tentorial opening, PF height, basion to reference line, opisthion to reference line, tentorium to reference line, trapezoid height, tentorial angle, occipital angle, basal angle, Boogaard’s angle, PF area, PF area above the reference line, PF area below the reference line, and areas 1–5 as described previously (Figure  1) [14]. …”
Section: Methodsmentioning
confidence: 93%
“…In a set of 2 publications, Markunas et al 9,10 examined the relationship between cranial base morphometrics and whole-genome expression profiles, finding that much posterior fossa morphology was heritable. Multiple genomic regions were strongly implicated with posterior fossa morphology using ordered subset analysis, including chromosomes 1 and 22.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the only form of treatment to alleviate symptoms is to perform a posterior fossa (PF) decompression surgery. The goal of this surgery is to expand the cranial base to provide additional room for the cerebellum while also restoring normal cerebrospinal fluid flow [23]. Another recent study suggested that Arnold Chiari Malformations can be prevented by pre-conceptional folic acid and Vitamin B 12 supplementation [14].…”
Section: Discussionmentioning
confidence: 99%